Clinical observation of external application of drugs at different periods in the treatment of phlebitis caused by iron sucrose infusion: a case report (分时段给予药物外敷治疗1例蔗糖铁所致静脉炎的效果观察) - CHEN Wen (陈雯); XU Qian (许倩); LU Ying (卢英) (中西医结合护理)
Therapeutic intravenous iron sucrose infusion is applied for the situation of iron malabsorption, or intolerance to oral iron in patients with iron-deficiency anemia. However, the extravasation of infusion drugs may lead to complications such as local swelling and pain. This paper reviewed the clinical treatment and nursing countermeasures of phlebitis caused by iron sucrose infusion in a patient. Ruyi Jinhuang ointment combined with magnesium sulfate and Hirudoid ointment were applied at different periods of treatment , and the swelling and pain relief at the back of the hand were observed. After 5 days of nursing intervention, the swelling and pain of the back of hand disappeared. (临床上对缺铁性贫血患者若出现不耐受或铁元素吸收不良情况可采用蔗糖铁静脉输液治疗, 但静脉药物外渗会引起局部组织出现肿胀、疼痛等并发症。本文总结1例蔗糖铁静脉输液治疗所致静脉炎的治疗与护理对策。通过分时段给予如意金黄膏联合硫酸镁、喜辽妥进行药物外敷, 同时观察患者手背肿胀及疼痛缓解情况。经护理干预5 d后, 患者手背肿胀疼痛消失。)